2017
DOI: 10.1016/j.wasman.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to maximize organic matter valorization in municipalities: Combination of urban wastewater with kitchen food waste and its treatment with AnMBR technology

Abstract: The aim of this study was to evaluate the feasibility of treating the kitchen food waste (FW) jointly with urban wastewater (WW) in a wastewater treatment plant (WWTP) by anaerobic membrane technology (AnMBR). The experience was carried out in six different periods in an AnMBR pilot-plant for a total of 536days, varying the SRT, HRT and the food waste penetration factor (PF) of food waste disposers. The results showed increased methane production of up to 190% at 70days SRT, 24h HRT and 80% PF, compared with W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Afterwards, the FW was pre-filtered using a mesh of 0.5 mm, similar to the one used for the UWW. Further details can be found elsewhere (Moñino et al, 2017).…”
Section: Characteristics Of the Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, the FW was pre-filtered using a mesh of 0.5 mm, similar to the one used for the UWW. Further details can be found elsewhere (Moñino et al, 2017).…”
Section: Characteristics Of the Substratesmentioning
confidence: 99%
“…The AnMBR plant, treating either UWW or UWW mixed with domestic FW, was operated for a long period within a wide range of operating conditions regarding both biological and filtration processes (Robles et al, 2013c;Giménez et al, 2011, Pretel et al, 2016Moñino et al, 2017).…”
Section: Overall Performance Of the Anmbr Plantmentioning
confidence: 99%
“…The plant was equipped with two 0.02 um pore size ultrafiltration membranes submerged in separate tanks. A detailed description of the pilot plant, feeding procedure, influent characterization and process results can be seen in Moñino et al [15,16].…”
Section: Pilot Plantmentioning
confidence: 99%
“…The feasibility of AnMBR technology for the joint treatment of food waste (FW) and urban wastewater has already been demonstrated in [14] and [15]. However, an in-depth insight into the process has not yet been obtained via model simulation, so that few relevant findings on the microbiology of this novel treatment are available.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a joint treatment of FW and urban WW has been performed in an AnMBR demonstration plant, generating high energy recovery yields in terms of methane and biogas production (Moñino et al, 2017). The notorious improve of the AD of urban WW once the FW addition was over, suggested that microbial population established during the experience was more efficient than the previous one established.…”
Section: Introductionmentioning
confidence: 99%